2014
DOI: 10.1128/genomea.00032-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Israeli Outbreak-Associated Vibrio vulnificus Biotype 3 Clinical Isolate BAA87

Abstract: Vibrio vulnificus is a seafood-associated pathogen that causes severe wound and intestinal infections. Biotype 3 of V. vulnificus emerged in 1996 as the cause of an Israeli outbreak associated with the handling of infected tilapia. Here, we describe the whole-genome sequence of the ATCC biotype 3 clinical isolate BAA87 (CDC9530-96).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The five Israeli samples—three human pathogenic biotype 3 strains and two environmental biotype 1 strains—were subjected to QUAST (Gurevich et al, 2013 ), a quality assessment tool for genome assemblies, using CMCP6 as a reference genome. We used the assembled genomes of two other biotype 3 strains, BAA87 and VVyb1, which were published by others for comparison purposes (Danin-Poleg et al, 2013 ; Phillips et al, 2014 ). The assembled genomes of biotype 3 strains (VV9-09, 491771, VV 4-03, BAA87, and VVyb1) showed similar characteristics and were different from the environmental strains (2322 and 101/04) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The five Israeli samples—three human pathogenic biotype 3 strains and two environmental biotype 1 strains—were subjected to QUAST (Gurevich et al, 2013 ), a quality assessment tool for genome assemblies, using CMCP6 as a reference genome. We used the assembled genomes of two other biotype 3 strains, BAA87 and VVyb1, which were published by others for comparison purposes (Danin-Poleg et al, 2013 ; Phillips et al, 2014 ). The assembled genomes of biotype 3 strains (VV9-09, 491771, VV 4-03, BAA87, and VVyb1) showed similar characteristics and were different from the environmental strains (2322 and 101/04) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The whole-genome sequence of BAA87 (GenBank accession no. JDSE00000000.1) has been published separately (55).…”
Section: Methodsmentioning
confidence: 99%
“…Nearly 22 and 56% of the core and accessory genomes encoded poorly characterized proteins (including proteins categorized as general function, unknown function, or not in COG database). The average size of the accessory genome of V. vulnificus strain was 1662 kbp (being smallest in the clinical strain ATCC 27562, 781 kbp, and largest in (Danin-Poleg et al, 2013;Phillips et al, 2014 the environmental strain 101/4, 2044 kbp). BLAST alignment of the non-core genomes against the reference clinical strain CMCP6 showed that most of the non-core genomic regions aligned to the large chromosome (data not shown).…”
Section: Core and Accessory Genomesmentioning
confidence: 99%
“…The five Israeli samples-three human pathogenic biotype 3 strains and two environmental biotype 1 strains-were subjected to QUAST (Gurevich et al, 2013), a quality assessment tool for genome assemblies, using CMCP6 as a reference genome. We used the assembled genomes of two other biotype 3 strains, BAA87 and VVyb1, which were published by others for comparison purposes (Danin-Poleg et al, 2013;Phillips et al, 2014). The assembled genomes of biotype 3 strains (VV9-09, 491771, VV 4-03, BAA87, and VVyb1) showed similar characteristics and were different from the environmental strains (2322 and 101/04) ( Table 2).…”
Section: Sequencing Quality and Read Mapping To Reference Genomesmentioning
confidence: 99%